Reducing, reusing, and recycling in the furniture industry: A mini-review - Pralat, Barabara; Anna Owsian; Rogozinski, Tomasz (Global Forest Journal, 2024)
This study explores sustainable practices within the furniture industry, focusing on the principles of reduce, reuse, and recycle. Through a comprehensive review of scholarly literature retrieved from databases like Scopus, Web of Science, and Google Scholar a moderate corpus of articles is identified. The analysis reveals a predominant emphasis on strategies aimed at minimizing resource consumption, extending product lifespans, and optimizing material recovery. While reduce, reuse and recycle serve as foundational pillars of sustainable furniture production, the literature also highlights complementary principles such as "rethink" and "refuse," urging critical reassessment and rejection of unsustainable practices. Despite the diversity in research interests and methodologies, the synthesis of findings underscores the need for standardization and comprehensive approaches to address environmental challenges throughout the furniture lifecycle. The study advocates for further research and collaboration to drive meaningful progress towards a more sustainable future for furniture production and consumption. This abstract encapsulates the key findings and implications of the study, providing a concise overview of the state of research on sustainable practices within the furniture industry. The aim of this short review is to analyse the scientific articles and their quantity relating to ecodesign in the furniture industry, with particular emphasis on the principles of reduce, reuse and recycle, as well as complementary concepts such as ‘rethinking’ and ‘refuse’.